Issues and Economic Role of Waqf In Higher Education Institution: Malaysian Experience - Harun, Farra Munna; Possumah, Bayu Taufiq; Mohd Shafiai, M Hakimi Bin; Nor, Abd Halim Mohd (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
As early as 1980, the Malaysianfederal government’s spending on education, was the highest in East Asia andhigher than the OECD average of 3.4% of GDP. This demonstrates that theMalaysian Government has big expenses from educational sector and respectivelyis amenability for Malaysian economic budget. In other side Waqf in Malaysia isone of large financial source that has not been fully explored. By using qualitative methodology through content analysis this paper attempt to explore the issues andeconomic role of Waqf in Malaysia, especially in Higher Education Institution(HEI) and attempt to study how Waqf fund empowering the education. Thisstudy found that taking the que from the institutions of Waqf, the explorationand development of waqf fund can be exalarate through the formation of formalorganizations at state and federal level and rearrange the Malaysian educationalbudget and policy to support the better quality of HEI.DOI: 10.15408/aiq.v8i1.2514